2020
DOI: 10.46827/ejmms.v5i3.830
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Service Quality on Athlete Satisfaction: An Empirical Results From Sports Facilities of Public Organizations

Abstract: <p>This study was carried out to examine the effect of service quality on the satisfaction of athletes. quantitative research patterns the simple random method was used in the study, the sample size consisted of 769 athletes trained in the Provincial Directorates of Youth and Sports and Municipalities in Antalya, Isparta, and Burdur. The Q-Sport-14 scale and customer satisfaction scale were used as data collection tools. Exploratory factor analysis was performed for validity to the scales and the interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…The results show that there is a positive and significant relationship between coaching efficiency and team cohesion and athlete satisfaction. Also, other research in this field has confirmed the relationship between coaching performance and athlete satisfaction as well as team cohesion in sports teams (Günel & Duyan, 2020;Junior et al, 2018;Kamis et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The results show that there is a positive and significant relationship between coaching efficiency and team cohesion and athlete satisfaction. Also, other research in this field has confirmed the relationship between coaching performance and athlete satisfaction as well as team cohesion in sports teams (Günel & Duyan, 2020;Junior et al, 2018;Kamis et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…Coach behaviors can affect athletes' perceptions, motivations, attitudes, and behaviors . The effectiveness of motivation is shown by two indicators, effort and satisfaction, and athletes while trying harder, express satisfaction with the sport (Günel & Duyan, 2020). Inoue et al (2020) Satisfaction is defined as a psychological structure that indicates the inner and psychological desire, and the athlete's decision to continue cooperation and satisfaction with it, which is influenced by various internal or external factors.…”
Section: Introductionmentioning
confidence: 99%
“…The above-depicted diagram shows the identity of independent variables, namely service quality, social environment, and financial support, whereas dependent variables consist of motivation, satisfaction, and athlete's performance. It is worth mentioning that previous studies have reported differing levels of these relations regarding the impact or effect of service quality on motivation or athlete performance [21], [22], the impact of social environment on motivation, and athlete performance [23]. Besides, financial support was also found to have made a significant contribution to motivation and athlete performance [24], [16], and so forth.…”
Section: Model Selection and Developmentmentioning
confidence: 90%
“…Since this study is conducted on athletes with various and multiple variables, we argue that it will contribute to the literature review in terms of being different from the researchers conducted for a single or two variables. For [22] the proposed research model examines the perception or liaison of service quality on athletes' satisfaction through their attitude and recommendations. In their results of the analyses based on averages, it was observed that service quality has a significant effect and the satisfaction level of athletes and their perceptions toward service quality was high.…”
Section: Discussionmentioning
confidence: 99%
“…Nilai regresi didapatkan sebesar R 2 = 0.582 dapat diartikan bahwa variabel gaya kepemimpinan pelatih dapat mempengaruhi variabel tingkat kepuasan atlet sebesar 58%, hasil ini memiliki arti gaya kepemimpinan pelatih berada pada tingkat yang cukup untuk mempengaruhi kepuasan atlet, dimana 42% yang dapat mempengaruhi kepuasan atlet dipengaruhi oleh faktor lain diluar gaya kepemimpinan pelatih, seperti: komitmen atlet dalam berlatih (Hundito & Professor, 2022), kebutuhan dasar atlet (Verner-Filion & Vallerand, 2018), motivasi diri atlet, kepercayaan diri atlet (Tamminen et al, 2019), serta pelayanan fasilitas olahraga (Günel & Duyan, 2020).…”
Section: Metodeunclassified